2018
DOI: 10.1161/jaha.118.010342
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Mediators of Racial and Ethnic Disparities in Congenital Heart Disease Outcomes: A Population‐Based Study in California

Abstract: Background Racial/ethnic and socioeconomic disparities exist in outcomes for children with congenital heart disease. We sought to determine the influence of race/ethnicity and mediating socioeconomic factors on 1‐year outcomes for live‐born infants with hypoplastic left heart syndrome and dextro‐Transposition of the great arteries. Methods and Results The authors performed a population‐based cohort study using the California Office of Statewide Health Planning and Devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 39 publications
4
105
1
1
Order By: Relevance
“…Indeed, in the United States, uninsured infants had a higher risk of mortality than those with private insurance . Moreover, state‐insured children had an increased risk of mortality and morbidity in their first year of life . Therefore, universal insurance in Quebec may have led to better access to care and early childhood interventions, thereby improving adult CHD outcomes and resulting pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the United States, uninsured infants had a higher risk of mortality than those with private insurance . Moreover, state‐insured children had an increased risk of mortality and morbidity in their first year of life . Therefore, universal insurance in Quebec may have led to better access to care and early childhood interventions, thereby improving adult CHD outcomes and resulting pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, state-insured children had an increased risk of mortality and morbidity in their first year of life. 37,38 Therefore, universal insurance in Quebec may have led to better access to care and early childhood interventions, thereby improving adult CHD outcomes and resulting pregnancy rates. Finally, since indications for cesarean sections and hospitalizations were not reported, firm conclusions on the cause of increased use of operative delivery and hospitalizations could not be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of concluding that genetic differences may drive these disparities, authors performed a mediation analysis to determine the contribution of Hispanic ethnicity to outcomes, and found that maternal education and insurance status explained a significant portion of the association of ethnicity and health outcomes. 21 Using the example of BPD, the reason for preterm birth (more than simply chorioamnionitis or preterm labor) may indeed differ by racial group and lead to differential risk of BPD. For example, the hormonal and immunologic milieu may differ among preterm infants born to women with preeclampsia compared with women with abruption or rupture of membranes.…”
Section: Social/environmentalmentioning
confidence: 99%
“…Our findings identified lower SES in the SVHD group compared to controls, with 50% of the SVHD sample of Hispanic ethnicity. Disparities have been identified in population-based studies in children with critical CHD in which SES explains a significant portion of the association between Hispanic ethnicity and worse health outcomes (35). However, controlling for SES in our analysis, there were still significant differences in mammillary body volumes and functional outcomes in the SVHD group compared to controls, and SES did not contribute to those variables.…”
Section: Discussionmentioning
confidence: 51%